2020
DOI: 10.1515/nanoph-2019-0506
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated-folic acid–modified black phosphorus quantum dots as near-infrared agents for dual-modality imaging-guided selective cancer cell destruction

Abstract: AbstractBiological systems have high transparence to 700–1100-nm near-infrared (NIR) light. Black phosphorus quantum dots (BPQDs) have high optical absorbance in this spectrum. This optical property of BPQDs integrates both diagnostic and therapeutic functions together in an all-in-one processing system in cancer theranostic approaches. In the present study, BPQDs were synthesized and functionalized by targeting moieties (PEG-NH2-FA) and were further loaded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Cellular and deep-tissue imaging [118] ultrasensitive detection of pH and temperature [119] Selectively target a variety of cancer cells [120] CDs Imaging-guided drug delivery [9] As a fluorescent nanoparticle probe for visual recognition of cancer cells [121] Mitochondrial targeting [98] Tumor therapeutics [50] Ultrasensitive detection of pH [122] Drug/gene delivery [123] Used as probes for analyzing biological systems [124] Ni dots Cellular imaging [125] P dots…”
Section: Gqdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellular and deep-tissue imaging [118] ultrasensitive detection of pH and temperature [119] Selectively target a variety of cancer cells [120] CDs Imaging-guided drug delivery [9] As a fluorescent nanoparticle probe for visual recognition of cancer cells [121] Mitochondrial targeting [98] Tumor therapeutics [50] Ultrasensitive detection of pH [122] Drug/gene delivery [123] Used as probes for analyzing biological systems [124] Ni dots Cellular imaging [125] P dots…”
Section: Gqdsmentioning
confidence: 99%
“…Unfortunately, the research on CDs with long-wavelength NIR emission has not been widely reported. For example, Wu et al [125] Therefore, fluorescence imaging has been considered as one of the most effective tools for observing biological processes in living cells. The preparation and modification of imaging materials have also become the focus of scientific researchers.…”
Section: Bioimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, after 4 h and an FA-PEG@BPQD@DOX intravenous (IV) injection, the temperature at the tumor section rose speedily along with the period of irradiation. The irradiation of 300 s at 808 nm (2 W/cm 2 ) speedily increased the temperature to 56.8 °C, which is enough to destroy human embryonic kidney (HEK 293T) cancer cells [ 46 ]. In another approach, BP was coated with polydopamine (PDA) and a novel nanocapsule BP@PDA-PEG-FA loaded with doxorubicin (DOX) as a classical drug for cervical cancer treatment was prepared, and configured with mercapto group (HS)-based targeting polymer, HS-PEG-FA.…”
Section: Surface Modification Of Black Phosphorusmentioning
confidence: 99%
“…Metabolic syndrome (MS) is a metabolic disorder syndrome, which was characterized by obesity, hyperglycemia, hypertension, dyslipidemia, and hyperuricemia, and this seriously endangers the health of patients [ 1 ]. It is a complex multisystem disease, and the difficulty lies between early intervention and multitarget therapy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%